Using Local-Wisdom Literature in Teaching English through Text-Based Method on Merdeka Belajar Curriculum - Halilah Lubis, Rehan; Darmawati , Besse (Al-Lisan: Jurnal Bahasa, 2023)
Literary text-based learning is interesting because literature learning in schools is often neglected. Literature learning often focuses on knowledge-based learning. The changing curriculum does not guarantee a change in the learning system in elementary school classrooms. Therefore, this study aims to describe the process of teaching and learning text-based literature at the elementary school level and its impact on students’ writing skills. Qualitative and quantitative descriptive methods were used. A qualitative method was used to describe the teaching and learning process in the classroom, while a quantitative method was used to assess learning outcomes. Techniques used were observation, interviews, and narrative writing tests, with the research object being three school teachers and 60 students from 3 schools in Samosir Regency. The results showed that the Seventh-Grade secondary school teachers in Samosir Regency do not yet understand text-based literature learning techniques fully, so teachers still use conventional methods. The results of teaching and learning activities on students’ ability to write narratives showed an average score of 73.27. This value has reached the Minimum Completeness Criteria (KKM) but has not yet been maximized because there are still obstacles.